The effects of physical activity on serum C-reactive protein and inflammatory markers : A systematic review - KASAPIS, Christos; THOMPSON, Paul D (Journal of the American College of Cardiology, 2005)
Physical activity is associated with a reduced incidence of coronary disease, but the mechanisms mediating this effect are not defined. There has been considerable recent interest in inflammation in the pathogenesis of cardiovascular disease. Some of the beneficial role of physical activity may result from its effects on the inflammatory process. We searched PubMed for articles published between 1975 through May 2004 using the terms exercise, physical activity, or physical fitness combined with C-reactive protein, inflammation, inflammatory markers, or cytokines. The review revealed 19 articles on the acute inflammatory response to exercise, 18 on cross-sectional comparisons of subjects by activity levels, and 5 examining prospectively the effects of exercise training on the inflammatory process. Exercise produces a short-term, inflammatory response, whereas both cross-sectional comparisons and longitudinal exercise training studies demonstrate a long-term "anti-inflammatory" effect. This anti-inflammatory response may contribute to the beneficial effects of habitual physical activity.